Are intellectual property rights stifling agricultural biotechnology in developing countries: IFPRI 2000-2001 Annual Report Essay - Pardey, Philip G.; Wright, Brian D.; Nottenburg, Carol (International Food Policy Research Institute, 2001)
For more than a century, plant breeders in government-funded research centers have sought out crop varieties with characteristics that might help poor farmers in developing countries grow more food. They have painstakingly bred and cross-bred these varieties through generations to achieve a desirable mix of characteristics. At an accelerating pace in the 1960s and 1970s the work of these breeders changed the developing world — the higher-yielding varieties of wheat, rice, and other food staples they produced helped avert catastrophic famine in Asia — and their work continues to improve the lives and livelihoods of millions of people. Now, however, critics of the newest tool in the agricultural researchers’ toolbox — genetic engineering — argue that the new environment for agricultural research may leave farmers in the developing countries out in the cold. The largely misplaced concerns that patents and other forms of intellectual property are currently severely constraining the freedom to operate in developing countries is diverting attention from more crucial issues for agricultural researchers working on staple food crops.